Od “tradit et acceptat ius in corpus” do “sese mutuo tradunt et accipiunt”. Ewolucja w ujęciu istotnego przedmiotu zgody małżeńskiej - Góralski, Wojciech (Biuletyn Stowarzyszenia Kanonistów Polskich, 2012)
In the article, the Author showed the evolution – from the Code of Canon Law of 1917 to the Code of Canon Law of 1983 – of the essential subject of the matrimonial consent. In the Code of Canon Law of 1917 there was biology conception of the marriage. According to the can. 1081 § 2, an essential subject of this consent are acceptance and transmission “ius in corpus”. Therefore, the material subject was the undying and the sole right to the body of the spouse, while the formal subject was sexual intercourse. According to the teaching of the Vatican Council II, marriage is a community of life and love conjugal. What is more, marriage is not only for the procreation and education of offspring, but also for the good of the spouses. Consequently, the phrase “ius in corpus” has been removed from the Cod e o f Canon Law of 1983.